An evaluation of physicians' engagement of children with asthma in treatment-related discussions. (September 2014) - Carpenter, Delesha M; Stover, Angela; Slota, Catherine; Ayala, Guadalupe X; Yeatts, Karen; Tudor, Gail; Davis, Stephanie; Williams, Dennis; Sleath, Betsy
Our objectives were to examine whether providers engage children with asthma in treatment-related discussions at the level children prefer (engagement concordance) and to determine whether engagement concordance is related to child, caregiver, and provider characteristics. Children with asthma ( n = 296) aged 8–16 years were recruited at five pediatric practices in North Carolina. Using audiotaped medical visit transcripts, we documented the number of treatment-related questions the providers asked the children. Children reported their preferred level of provider engagement. A logistic generalized estimating equation was used to determine which variables predicted engagement concordance. Most children (96.6%) wanted to be involved in treatment-related discussions. One-third of the providers did not ask children any treatment-related questions. Only 36.1% of provider–child dyads were concordant. Most discordant dyads were under-engaged (83.1%). Better engagement concordance was observed among older children (odds ratio (OR) = 1.19, 95% confidence interval (CI) (1.07, 1.33)), male children (OR = 1.67, 95% CI (1.03, 2.70)), and among providers with fewer years in practice (OR = .97, 95% CI (.94, .99)). Providers engaged in treatment-related discussions with younger children and females less frequently than these children preferred. Providers should ask children how much they want to be involved in treatment-related discussions and then attempt to engage children at the level they prefer.